2022
DOI: 10.1093/jn/nxab367
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dietary Choline Intake, Contributing Food Items, and Associations with One-Carbon and Lipid Metabolites in Middle-Aged and Elderly Adults: The Hordaland Health Study

Abstract: Background Choline is an essential nutrient for humans and is involved in various physiological functions. Through its metabolite betaine, it is closely connected to the one-carbon metabolism and the fat-soluble choline form phosphatidylcholine is essential for very-low-density-lipoprotein synthesis and secretion in the liver connecting choline to the lipid metabolism. Dietary recommendations for choline are not available in the Nordic countries primarily due to data scarcity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…At baseline, males had higher plasma DMG (p = 0.001) and methionine (p = 0.003) compared to females and at week 12 the higher plasma DMG (p < 0.001) in males remained (Table 3). A community-based study conducted by Van Parys et al in western Norway found that both middle-aged and elderly males had higher plasma methionine compared to females with a choline intake of 260 mg per day assessed by FFQs [72]. Unlike the present study, there were no changes in plasma DMG reported between males and females.…”
Section: Plasma Dimethylglycine Decreased In Response To the Dash Die...contrasting
confidence: 82%
“…At baseline, males had higher plasma DMG (p = 0.001) and methionine (p = 0.003) compared to females and at week 12 the higher plasma DMG (p < 0.001) in males remained (Table 3). A community-based study conducted by Van Parys et al in western Norway found that both middle-aged and elderly males had higher plasma methionine compared to females with a choline intake of 260 mg per day assessed by FFQs [72]. Unlike the present study, there were no changes in plasma DMG reported between males and females.…”
Section: Plasma Dimethylglycine Decreased In Response To the Dash Die...contrasting
confidence: 82%
“…It should be noticed that the great majority of the identified studies released after 2015 are based on data obtained in previous decades (1992–2015), and cannot be relied on in discussing current trends in choline intake. The studies were conducted in nine European countries only: Poland [ 18 , 24 , 26 , 34 ], Norway [ 17 , 28 ], Germany [ 13 ], Spain [ 27 ], Sweden [ 54 ] Romania [ 31 ], Belgium [ 33 ], Italy [ 66 ] and the United Kingdom [ 35 ]. Eight studies have reported choline intake in adults [ 17 , 18 , 24 , 27 , 28 , 54 , 66 ], one study measured choline intake in children [ 31 ], and four studies have recorded choline intake in pregnant women [ 13 , 33 – 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in nine European countries only: Poland [ 18 , 24 , 26 , 34 ], Norway [ 17 , 28 ], Germany [ 13 ], Spain [ 27 ], Sweden [ 54 ] Romania [ 31 ], Belgium [ 33 ], Italy [ 66 ] and the United Kingdom [ 35 ]. Eight studies have reported choline intake in adults [ 17 , 18 , 24 , 27 , 28 , 54 , 66 ], one study measured choline intake in children [ 31 ], and four studies have recorded choline intake in pregnant women [ 13 , 33 – 35 ]. Among the twenty-one studies measuring choline intake in non-European countries, the majority (52%) were conducted in the USA [ 19 , 20 , 25 , 32 , 55 – 57 , 62 – 65 ], while the others were carried out in Palestine [ 58 ], South Africa [ 59 ], Australia [ 36 , 60 ], Mexico [ 23 ], Taiwan [ 16 ], Iran [ 22 , 29 ], Canada [ 21 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Choline, as an essential nutrient, 14 can be divided into fat-soluble choline ( phosphatidylcholine and sphingomyelin) and water-soluble choline (free choline, phosphocholine, and glycerophosphocholine). 15,16 Choline has important and diverse functions in both cellular maintenance and growth 15,17 that are related to diverse diseases, including neurological disorders, 18 liver diseases, 19 and tumor progression. 20 Deficiency of choline is proposed to have carcinogenic effects, and poten-tial mechanisms include enhanced apoptosis, 14 decreased cell proliferation, 21 increased DNA damage, 22 and altered gene expression.…”
Section: Introductionmentioning
confidence: 99%